The generation of novel epialleles in plants: the prospective behind re-shaping the epigenome - Alessio Baldini; Filippo Battaglia; Giorgio Perrella (Frontiers in Plant Science)
Chromatin organization is a relevant layer of control of gene expression during plant development. Chromatin states strictly depend on associated features such as DNA methylation, histone modifications and histone variants. Thus, epigenome editing has become of primary interest to alter gene expression without disrupting genomic sequences. Different tools have been developed to address this challenge, starting with modular Zinc Finger Proteins (ZFPs) and Transcription Activator Like Effectors (TALEs). However, the discovery of CRISPR/Cas9 system and the adaptability of technologies based on enzymatically dead Cas9 (dCas9) have paved the way towards a reliable and adaptable epigenome editing in a great variety of organisms. In this review, we will focus on the application of targeted epigenome editing technologies in plants, summarizing the most updated advances in this field. The promising results obtained by altering the expression state of targets involved in flowering time and abiotic stress resistance are crucial not only for elucidating the molecular interactions that underly chromatin dynamics, but also for future applications in breeding programs as an alternative route to genetic manipulation towards the achievement of higher quality crops particularly in terms of nutritional properties, yield and tolerance.